IDENTIFIKASI CACAT PADA GENTENG WENDIT DENGAN DIAGRAM PARETO - Retno, Dyah (Jurnal Gamma, 2009)
One of centrale of home industry in Malang is UD. BJ Mendit on Mendit Barat, Kec. Pakis withit?s roof production process. From the observation that the researcher do into UD. BJ Mendit,finded that the production process had been doing often with technical and non technical problemsthat make some failed roof product. Purposes of this research are identifying types of roof failedproduct, analysing main cause of roof failed product with Pareto diagram. From the steps had done,finded that the biggest failed criterion is keropos. Keropos is caused by lack of skill and correctnessof worker on processing the raw material, can also caused by process execution which not fullycorret so that produce critical process to be repaired first to increase the quality of Mendit?s roof.